If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3y = 133 Solving 2x + 3y = 133 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 2x + 3y + -3y = 133 + -3y Combine like terms: 3y + -3y = 0 2x + 0 = 133 + -3y 2x = 133 + -3y Divide each side by '2'. x = 66.5 + -1.5y Simplifying x = 66.5 + -1.5y
| x^2-y^2-25=0 | | 2(-6v+7)=-2-2(-6+8v) | | (3,4)=1 | | 2x-1=2(x-1/2) | | -81-30= | | X^3+3X-2=X^3+X^2+X+1 | | (4x+5x-3)(4x-7)(9x+10)= | | -8=2v+6 | | ((a)(a))+((3)(3))=((7)(7)) | | 6y-13=27 | | -6-3-2k+4=18 | | -8.34-10y=-50 | | 4(x+2)-3x+6=x+8 | | 1+2b-6b=9 | | 2g+2(-7+5g)=1g | | (3k-4)-(5k+2)= | | -18=-2w | | 4b-2b=18 | | 16=64/x | | 4(x+6)-2(x-2)=2(x+7)-2 | | y=-7x^2+38x+24 | | 4(6x-7)(4x+3)= | | 5(x+2)+3(2x+4)=3(2x+16)-1 | | y-9=12-6y | | X^2-3X+2=3X^2+X-4 | | -(1-8x)+7=-6x+4(4x+4) | | x=-1/3-234 | | Y-5y-5=-21 | | 21=-6x-3 | | 58.38-2y=50 | | -30=3x | | 6+4b=45b |